Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1001/jamasurg.2021.3655
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Adalimumab in Conjunction With Surgery in Moderate to Severe Hidradenitis Suppurativa

Abstract: IMPORTANCE Surgery is a mainstay in the management of hidradenitis suppurativa (HS). Adalimumab is the first drug approved for HS.OBJECTIVE To investigate the efficacy and safety of adalimumab in combination with wide-excision surgery followed by secondary intention healing. DESIGN, SETTING, AND PARTICIPANTSThe Safety and Efficacy of Adalimumab for Hidradenitis Suppurativa Peri-Surgically (SHARPS) trial was a phase 4, randomized, double-blind, placebo-controlled study of adalimumab in conjunction with surgery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 29 publications
(79 reference statements)
5
67
0
11
Order By: Relevance
“…A Phase 4 trial, the Safety and Efficacy of Adalimumab for Hidradenitis Suppurativa Peri-Surgically (SHARPS) trial, included 206 patients and found that adalimumab was efficacious in conjunction with wide-excision surgery, and there was no increased risk of adverse events or postoperative complications. 6 This study supports that there is no need to interrupt adalimumab treatment before or post HS surgery.…”
Section: Tnf-α Inhibitors 21 | Adalimumabsupporting
confidence: 77%
“…A Phase 4 trial, the Safety and Efficacy of Adalimumab for Hidradenitis Suppurativa Peri-Surgically (SHARPS) trial, included 206 patients and found that adalimumab was efficacious in conjunction with wide-excision surgery, and there was no increased risk of adverse events or postoperative complications. 6 This study supports that there is no need to interrupt adalimumab treatment before or post HS surgery.…”
Section: Tnf-α Inhibitors 21 | Adalimumabsupporting
confidence: 77%
“…There was no increased rate of postoperative wound infection, surgical complication, or hemorrhage between the two groups. This study, the most robust of its kind, supports that adalimumab use in the perioperative setting may indeed be safe and efficacious, thus supporting that no cessation of adalimumab is necessary before surgery 27 …”
Section: Surgical Outcomes For Hidradenitis Suppurativa and The Gaps ...supporting
confidence: 62%
“…This study, the most robust of its kind, supports that adalimumab use in the perioperative setting may indeed be safe and efficacious, thus supporting that no cessation of adalimumab is necessary before surgery. 27 Further investigation with similar studies is still required for other biologics to determine the appropriate timing of holding the medications, or if this is necessary at all. Very few studies report what, if any, perioperative medication changes have been made and more importantly, the timing of these changes.…”
Section: Perioperative Medication Managementmentioning
confidence: 99%
“…Pharmacological treatment includes topical treatment (clindamycin), systemic antibiotics (tetracycline, clindamycin‐rifampicin), anti‐inflammatory agents (corticosteroids), and biologics (anti‐TNF, ustekinumab). Combination therapy with a biologic, including adalimumab, and surgery has been shown to be effective 40–45 . The majority of patients (84.3%) in this study had received pharmacological treatment for HS prior to adalimumab administration.…”
Section: Discussionmentioning
confidence: 95%
“…Combination therapy with a biologic, including adalimumab, and surgery has been shown to be effective. [40][41][42][43][44][45] The majority of patients (84.3%) in this study had received pharmacological treat-…”
Section: Serious Any Seriousmentioning
confidence: 92%